Reconstructing recent environmental changes using non-biting midges (Diptera: Chironomidae) in two high mountain lakes from northern Patagonia, Argentina - Montes de Oca, Fernanda (2018)
Remote lakes of northern Patagonia are ideal sites for examining climate- and non-climate-driven changes in aquatic ecosystems because there is little evidence of human influence and there is no detailed information on recent environmental trends in the region (i.e. the last 200 years). Subfossil chironomids (Diptera: Chironomidae) are useful paleoindicators due to their specific response to numerous environmental factors. Here, we analyze the chironomid subfossil assemblages from two remote lakes located in different environmental settings in Nahuel Huapi National Park of northern Patagonia, Argentina. Chironomids combined with sedimentary pigments (chlorophyll derivatives and total carotenoids) and organic matter provided information on the environmental history of the lakes for the last ca. 200 years. The 210Pb chronology and tephra layers are used to establish the chronology of changes in the chironomid assemblages associated to different environmental factors that impacted the area during the period covered by the study. The deposition of volcanic ash affected the abundance and composition of chironomid assemblage throughout the record of both lakes. However, changing climate conditions and human activities are also responsible for chironomid changes in the last 50 years.